1994
DOI: 10.1111/j.1751-0813.1994.tb03403.x
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy against sheep lice (Bovicola ovis) and fleece wetting of six shower dip preparations

Abstract: The relative efficacy of 6 shower dip chemicals most frequently used for the treatment of sheep lice (Bovicola ovis) in Western Australia was examined. Groups of 20 sheep infested with lice were treated with products containing either alphamethrin, cyhalothrin, diazinon or diazinon plus piperonyl butoxide and rotenone, formulated as emulsifiable concentrates, and with products containing either coumaphos or magnesium fluorosilicate, formulated as wettable powders. All treatments were applied through a shower d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

1998
1998
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 6 publications
0
8
0
Order By: Relevance
“…Rotenone has been proposed as a treatment for the honeybee mite Varroa destructor [65], the Atlantic salmon Plathyhelminth Gyrodactylus salaris [66], cattle hypodermosis [67] and the sheep louse Bovicola ovis [68].…”
Section: Effects Of Flavonoids On Other Para-sitesmentioning
confidence: 99%
“…Rotenone has been proposed as a treatment for the honeybee mite Varroa destructor [65], the Atlantic salmon Plathyhelminth Gyrodactylus salaris [66], cattle hypodermosis [67] and the sheep louse Bovicola ovis [68].…”
Section: Effects Of Flavonoids On Other Para-sitesmentioning
confidence: 99%
“…Higgs et al 4 found that wettable powder products were less effective at eradicating lice than four emulsifiable concentrate products. The poorer efficacy was attributed to the poorer wetting achieved, both in vivo and in vitro, with the powder products.…”
Section: Ddtmentioning
confidence: 99%
“…On days 22 and 23 after shearing (day 0 of the trial), the 200 sheep were weighed, ear-tagged and lice counted by a standard method. 4 The sheep were stratified on louse count into five categories, further stratified within category on shorn body weight, divided into groups of 10 sheep and allocated randomly to 10 treatment groups.…”
Section: Shower Dipping Experimentsmentioning
confidence: 99%
See 2 more Smart Citations